Human Antibody Response Against Aedes aegypti D7 Salivary Proteins - Morton, Danielle; Rozo, Paula; Londono-Renteria, Berlin (My University, 2017)
Dengue is one of the most geographically significant mosquito transmitted diseases caused by dengue virus (DENV). In endemic areas of tropics and subtropics, this disease has become the leading cause of morbidity and mortality. In the Americas, DENV is primarily transmitted to humans by Aedes aegypti and Ae. albopictus mosquitoes. During blood feeding, the female mosquito injects saliva into the human skin to facilitate meal intake. The salivary proteins (mSP) stimulate immune responses that may lead to antibody production and modulation of cellular and cytokine function with a strong effect on viral infectivity. Previous studies have showed that the salivary allergen D7 exhibits anti-viral properties for DENV in the human skin. It is hypothesized that in endemic settings, after repeated exposure to mosquito bites, human hosts develop an immune response against mSP that can enhance or block viral infectivity.